Keabsahan Tanda Tangan Digital dalam Transaksi Bisnis - Cok Trisna Dewi Pemayun; Putu Eka Trisna Dewi (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2025)
Purpose: The aim of this research is to examine and analyze the regulation of electronic signatures in law in Indonesia and the legal power of electronic signatures Methodology: The research used legal research with normative aspects, which is a step to finding a legal rule, legal principles, or legal doctrines to answer the legal issues faced. This legal research was conducted using descriptive-analytical research specifications. This study's data collection method was library research and qualitative data analysis. Results: The regulations regarding electronic signatures in Indonesian law are contained in various laws and regulations. The legal power of a valid Electronic Signature is as long as it meets the requirements in Article 11 paragraph (1) of Law Number 1 of 2024 concerning Information and Electronic Transactions, then in Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, it is stipulated that there are 2 types of Electronic Signatures, namely certified and uncertified. Certified electronic signatures must also meet the validity of the legal force and legal consequences of electronic signatures as required in Article 59 paragraph (3), using electronic certification made by the Indonesian Electronic Certificate service provider and made using a certified electronic signature maker. Limitations: This study is limited to the validity of digital signatures in business transactions in Indonesia. Contribution: This research helps contract designers draft electronic contracts and provides a reference for judges when examining cases related to the validity of digital signatures. Theoretically, it contributes to the development of business law science, especially contract law.